Chitosan-Fe-Al-Mn metal oxyhydroxides composite as highly efficient fluoride scavenger for aqueous medium. (15th July 2019) - Chaudhary, Mohit; Rawat, Shweta; Jain, Nishant; Bhatnagar, Amit; Maiti, Abhijit
Graphical abstract: Highlights: Chitosan helps to improve the fluoride adsorption by metal oxides nanoparticles. Agglomeration of nanoparticles reduces after dispersion into porous polymer. Interaction among chitosan and metal oxides revealed by XPS analysis. Polymeric barrier causes unaffected adsorption under ionic strength. Faster adsorption due to less agglomeration and high porosity in polymer matrix. Abstract: Nano-particles are highly efficient fluoride adsorbents, but agglomerate easily due to their high surface activity and are difficult to separate from aqueous medium after use. Mixed-metals oxyhydroxides nano-particles were prepared into a natural polymeric matrix of chitosan to overcome these problems. Hydrous mixed-metal oxyhydroxides, loaded chitosan composite (Fe-Al-Mn@chitosan) was prepared using abundantly available laterite clay and waste from steel industry via co-precipitation method. Fluoride removal using Fe-Al-Mn@chitosan composite followed Freundlich isotherm model which revealed multilayer adsorption on heterogeneous surface sites. Fe-Al-Mn@chitosan exhibited maximum adsorption capacity of 40±0.5 mg/g, while if only the inorganic mass fraction of composite was considered; the value reached 55±0.5 mg/g. Fluoride adsorption on Fe-Al-Mn@chitosan followed the pseudo-second order kinetics with rapid adsorption. No significant effect of other competitive ions was observed on F − adsorption using Fe-Al-Mn@chitosan composite. The composite adsorbent is found to be effective to produce drinking water from fluoride contaminated groundwater.